The impact of a Higher Education Institution on Socioeconomic Development – the Study Case of the Polytechnic Institute of Beja, Portugal - Sandra Saúde; Carlos Borralho; Isidro Féria; Sandra Lopes (Copernican Journal of Finance & Accounting, 2014)
It is widely recognized that the investment in human capital, innovation, and knowledge transfer is essential to sustainable development and growth. Within this context, the role and action of Higher Education Institutions (HEIs) are vital. This paper aims to reflect on the role and impact of higher education on regional development, based on the reality of public higher education in Portugal and, more specifically, the case study of the Polytechnic Institute of Beja (IPBeja). This institution belongs to the subsystem of polytechnic higher education and is located in a region that has one of the lowest economic ratios and population density in Europe.